PENGEMBANGAN E-MODUL FLIP PDF UNTUK SISWA FLEGMATIS PADA MATERI PECAHAN KELAS VII MTs NURUL BAHRI - Kodai, Muhaimin; Hulukati, Evi P.; Djakaria, Ismail (Universitas Bhinneka PGRI, 2025)
This study is directed at the development of a digital learning resource in the form of a mathematics e-module utilizing the Flip PDF application, specifically designed to accommodate the learning tendencies of students with a phlegmatic personality type on fraction topics at the junior high school level. The product development employed a Research and Development approach using the ADDIE framework, which consists of needs analysis, design planning, product creation, classroom implementation, and outcome evaluation stages. The research participants were seventh-grade students of SMP/MTs at MTs Nurul Bahri Kabila Bone who were identified as having phlegmatic personality characteristics. Data collection techniques included product feasibility assessments conducted by subject-matter experts and media experts, questionnaires capturing teacher and student responses, as well as personality identification instruments based on Florence Littauer’s theory. The collected data were analyzed using descriptive quantitative methods. The results indicate that the developed e-module achieved a very high level of feasibility, as evidenced by average validation scores of 3.40 from media experts and 3.60 from subject-matter experts. Practicality testing showed that teachers provided a perfect response rate of 100%, categorized as very practical, while student responses reached 85.49%, categorized as practical. Therefore, the Flip PDF–based mathematics e-module developed in this study is considered feasible, practical, and effective for use as a learning resource to support fraction learning for junior high school students with a phlegmatic personality type.